Design and Construction of Guest Friendly Robot for Front Office Service on Campus Based on IoT - Putri Purwani, Dea Nanda; Buaton, Relita; Milli Alfhi Syari (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
Amid the rapid advancements of the digital era, Internet of Things (IoT) technology has emerged as one of the most significant innovations, enabling electronic devices to connect and interact intelligently. This study aims to design and develop an IoT-based guest reception robot intended for front office services at the campus. The robot is designed as a prototype capable of welcoming guests, saying "welcome," and providing four key pieces of information about the campus. Utilizing components such as ESP32 and ultrasonic sensors, the robot is expected to enhance service efficiency while also offering a more interactive experience for campus visitors. The implementation of IoT in this robot is not only intended to improve visitor services but also to promote technological innovation within the campus environment. This study also explores the integration of hardware and software, as well as the features and functions needed to meet the requirements of front office services. Thus, this research is expected to serve as a foundational step toward creating a more modern and innovative campus.